ВАРІАТИВНІСТЬ ВИБОРУ ВИКОНАВЧОЇ СТРУКТУРИ БАГАТОРІВНЕВОГО ВИПРЯМЛЯЧА З ОБМЕЖЕНИМ ДІАПАЗОНОМ РЕГУЛЮВАННЯ ВИХІДНОЇ НАПРУГИ - К.О. Липківський; А.Г. Можаровський (Праці Інституту електродинаміки Національної академії наук України)
Harmonization of the requirements of certain groups of electrical and electrotechnological consumers of electricity with the current supply conditions requires in many cases the use of converters. Prominent among the systems designed to purposefully change the supply voltage of such consumers (regulation, stabilization) are converters with transformer-and-switches executive structure or tap changing (smart) transformers, which use discrete-time control, in particular so-called multi-level AC rectifiers (MLR). In the synthesis of MLR the main problem is to determine the optimal law of sectioning of the secondary envelope of its transformer. The paper analyzes the features of MLR decomposition into two functionally identical blocks under the given limitation of the output voltage control range and its difference from the decomposition of wide-range MLRs. The a priori variety of circuit technical solutions of such MLRs is determined. New MLRs with high efficiency of semiconductor switch elements use are offered. Ref. 14, fig. 2, tables 3.